(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2022)
Interprofessionelle Kooperation von Lehrkräften als Qualitätsmerkmal inklusiver Schule findet sich in der vorbereitenden Hochschullehre selten. Dass Hochschullehre kooperativ angelegt werden kann, wird im Artikel anhand des Zusatzstudiums Inklusion – Basiskompetenzen (ZIB) der Universität Regensburg1 aufgezeigt. Im Beitrag wird die Konzeption des ZIB, v. a. die Bedeutung der Tandemlehre von Sonder- und Regelschullehrkraft, vorgestellt und mit Erfahrungen der Dozierenden sowie der Studierenden ergänzt. In inclusive schools, interprofessional cooperation between teachers is an important quality feature. But in preparatory university teaching collaboration is rarely implemented. The article shows that university teaching can be designed in a cooperative way by the example of the supplementary study programme “Inclusive education – basic skills (ZIB)” at Universität Regensburg. This programme relies on tandems of lecturers from special education and regular school teachers. The article presents the concept of the ZIB, especially the importance of the tandem teaching, and the experiences of lecturers and students.